Effective Strategies in Professional Financial Management (A service approach to Penambak Udang in Karang Gading Village) - sati, Dea sarah; Batubara, Maryam; Sirait, Frida Yanti (Universitas Islam Negeri Sumatera Utara, 2024)
Effective financial management is an important aspect of business success, including in the fisheries sector such as shrimp farming. Karang Gading Village, Deli Serdang Regency, is one of the main Vaname shrimp farming locations in Indonesia. However, many shrimp farmers in the village face challenges in managing their finances professionally. Through a community service approach, we aim to provide assistance and training to shrimp farmers in developing effective strategies in their financial management. This approach involves a series of trainings, consultations, and guidance on the basic principles of professional financial management. The outcome of this activity is expected to improve shrimp farmers' understanding and skills in managing their finances, so that they can achieve financial stability and improve the sustainability of their business.